2021
DOI: 10.1007/s00423-021-02219-4
|View full text |Cite
|
Sign up to set email alerts
|

Local control of hepatocellular carcinoma and colorectal liver metastases after surgical microwave ablation without concomitant hepatectomy

Abstract: Purpose Microwave ablation (MWA) is an accepted technique in the multimodal treatment of hepatocellular carcinoma (HCC) and colorectal liver metastases (CRLM). Study endpoints were to evaluate the local efficacy of surgical MWA in selected patients with oligonodular disease without the combination of liver resection to allow a clear interpretation of the follow-up imaging and compare it to the results on percutaneous MWA available in the literature. Methods Consecutive MWA-only procedures performed between May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…First, the exposure of tumors in difficult positions, such as segments VII, VIII, and I, could be challenging and need hepatic mobilization, and tumors in these difficult locations may often be excluded by some high‐quality studies 18 ; second, it is hard to puncture the tumor following the trajectory in coordination with laparoscopic intraoperative ultrasound. 19 , 20 Therefore, the localization of laparoscopic intraoperative ultrasound required experienced doctors and possessed a learning curve. In this study, all recruited operations were completed by the same surgeon and his team to ensure consistent quality.…”
Section: Discussionmentioning
confidence: 99%
“…First, the exposure of tumors in difficult positions, such as segments VII, VIII, and I, could be challenging and need hepatic mobilization, and tumors in these difficult locations may often be excluded by some high‐quality studies 18 ; second, it is hard to puncture the tumor following the trajectory in coordination with laparoscopic intraoperative ultrasound. 19 , 20 Therefore, the localization of laparoscopic intraoperative ultrasound required experienced doctors and possessed a learning curve. In this study, all recruited operations were completed by the same surgeon and his team to ensure consistent quality.…”
Section: Discussionmentioning
confidence: 99%
“…The couinaud's segments 1, 7, and 8 were defined as the posterosuperior segments [15]. Contact with the hepatic vein (HV)/ inferior vena cava (IVC) was defined as present when a lesion was in direct contact with the first or second trunk of the HV or IVC.…”
Section: Definitionsmentioning
confidence: 99%
“…However, local tumor recurrence is a major setback associated with ablation therapy, which occurs in MWA and RFA. Local treatment failure ranging from 20 to 60% has been reported with RFA [12,13] and 6 to 20% with MWA [11,14,15]. The local recurrence (LR) rate may be lower for patients with CRLM treated with MWA than those treated with RFA [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the protumorigenic environment resulting from a sublethal ablation may be reflected also at a systemic level due to the diffusion of cytokines in the serum. Indeed, experimental studies demonstrated that the growth of distant cancers was found related to the different parameters of ablation performed in the liver (85)(86)(87)(88)(89). The key immune modulators produced by damaged liver tissue after ablation are the HSPs, which are expressed as a defense against hyperthermia and may serve as a prognostic marker of ablation, although warranting further tests in clinical settings (90).…”
Section: Immunological Implications Of Locoregional Treatmentmentioning
confidence: 99%